Lending methodology for SMMEs in the South African construction industry - Naphambo, Edward James (My University, 2011)
A lending methodology refers to the design of the service and the way in which it is delivered. Components of a lending methodology include: product design and pricing; collateral; screening mechanisms; disbursement and repayment procedures; and delinquency management procedures. Although finance is available from various institutions namely government agencies, Non Governmental Organisations (NGOs) and the private sector, Small Medium Micro and Survivalist enterprises (SMMEs) in the construction industry are still experiencing problems in accessing finance to fund their projects. Current domestic and international literature suggests that the lack of finance is attributed to political interference and inefficiencies in government and NGOs operations; mistrust of third party agencies by SMMEs and ineffective service provision. Commercial banks on the other hand are ideally placed to provide finance to SMMEs because they are well regulated institutions and have vast branch networks. However, commercial banks are wary of providing microfinance to SMMEs because they do not have the appropriate lending methodology to provide the required finance and still make a return adequate enough to make the services provided to SMMEs sustainable. By administering questionnaires to regional managers of the SMME divisions of various commercial banks in the Greater Johannesburg Metropolitan Area (GJMA), this research report investigates whether commercial banks in the GJMA have the appropriate lending methodology to provide microfinance to SMMEs in the construction industry. This study concludes that commercial banks do not have the appropriate lending methodology to provide microfinance to SMMEs in the construction industry. The findings of the study further indicate that an opportunity exists to create lending methodology for SMMEs in the construction industry by reducing transaction costs and adopting relationship lending techniques utilised by Micro Finance Institutions (MFIs) internationally